Preparation of plasmonic metal / semiconductor hybrid nanostructures : Ag @ TiO2 @ Cu2O nanoprisms - Yong, Si Jie (2016)
Hybrid plasmonic metal / oxide semiconductor core-shell nanostructures have garnered extensive attention owing to their unique properties and limitless potential applications. Past researches tended to overlook the importance of anisotropic nanostructures such as nanoprisms despite their properties having the potential to be tuned to satisfy different application requirements. The pairing of silver (Ag) and titanium dioxide (TiO2) in a core-shell design is highly promising due to enhanced photocatalytic activities. Prior research revealed that coupling copper oxide with TiO2 could further boost the photocatalytic proficiencies. Hence, novel Ag @ TiO2 @ Cu2O hybrid nanoprisms were synthesised by a four-step approach, beginning with liquid phase synthesis of Ag nanoparticles. Photo-induced transformation of spherical Ag nanoparticles into nanoprisms was adopted before the coating of TiO2 shells and Cu2O nanoparticles respectively. The prepared nanostructures were characterised by transmission electron microscopy (TEM) and UV-Vis analysis. TEM imaging revealed a good size distribution of triangular Ag-core nanoprisms with Cu2O nanoparticles embedded in 6-7 nm-thick TiO2 outer shells. The effects of varying precursor amounts were also investigated via UV-Vis analysis. Two methods were described for the final step of depositing Cu2O nanoparticles. Further studies have to be conducted to determine the stability of the nanoprisms for each route. Additionally, the enhancement of photocatalytic activities, if any, by the presence of Cu2O nanoparticles has to be established.